Better business decisions from data : statistical analysis for professional success - Kenny, Peter, 1935- (Expert's voice in data analysis., 2014)
This book discusses what statistics are really saying or not saying. It shows how to use statistical data to improve small, every-day management judgments as well as major business decisions with potentially serious consequences. This book lays a foundation for understanding the importance and value of big data and shows how mined data can aid business opportunity. Topics covered include: how data is collected, sampled, and best interpreted, to obtain information, with known reliability, for the basis of decision making; the basics of probability, sampling, reliability, regression, distribution and other statistical techniques essential for decision making in all aspects of business; how statistics can help assess the probability of a successful outcome; how to make effective forecasts based on the data at hand; why certainty is illusive and statistical results can be misleading; how to spot the misuse or abuse of statistical evidence in advertisements, reports, and proposals; how to commission a statistical analysis and what it can--and can't--do. This book is a guide for managers and professionals in business and industry; for students of disciplines that require some knowledge of statistics, economics, finance, political science, physics, biology, and more; and for general readers who simply wish to have a more informed view of statistics.